Clinical classification of galvanic manifestations, emerging in the oral cavity after the installation of metal inclusions (lecture) - Тимофеев, Алексей Александрович; Ушко, Наталия Алексеевна; Тимофеев, Александр Алексеевич; Ярифа, Мария Алексеевна; Кабанчук, Сергей Викторович; Беридзе, Бека (Actual Dentistry, 2019)
Purpose: to tell students, interns and doctors about the galvanic manifestations that occur in the oral cavity in the presence of non-removable metal prostheses made of base metal alloys. Methods. Potentiometric, as well as clinical and laboratory examinations of patients. Results. Galvanic pathology was studied, which is observed in patients with various dental diseases if they have metal inclusions in their oral cavity. Conclusions. it is proposed to use the clinical classification of galvanic manifestations. Key words: Dental implants, tumors, tumor-like diseases, inflammatory diseases, metals, non-removable dentures, saliva, oral cavity, mucous membrane, pathology, inflammation, complications, immunity, galvanism, galvanosis.